Development of a new patient‐reported outcome (PRO) measure on the Impact of Nighttime Urination (INTU) in patients with nocturia—Psychometric validation. Issue 5 (25th March 2018) - Bennett, Jason B.; Gillard, Kristin Khalaf; Banderas, Benjamin; Abrams, Steven; Cheng, Linda; Fein, Seymour
Abstract : Aims: To psychometrically evaluate the Impact of Nighttime Urination (INTU) questionnaire, a new patient‐reported outcome measure developed to assess the impact of nocturia on health and functioning in a multicenter, behavioral modification (fluid restriction) study. Methods: Participants aged 50‐95 years with at least two voiding episodes/night for ≥6 months completed voiding diaries and the INTU on 3 consecutive days during weeks 1 and 2 (same day recall) and completed the Pittsburgh Sleep Quality Index (PSQI) and Nocturia Quality of Life Questionnaire (N‐QOL) at baseline and days 8 and 15. Psychometric evaluations of the INTU were conducted. Results: Rasch analysis showed the INTU to be a unidimensional construct, with most items located on the severe end of the symptom severity continuum. In addition to an Overall Impact Score (10 items), exploratory factor analysis affirmed by confirmatory factor analysis identified two domains: Daytime (six items) and Nighttime (four items) Impact Scores (comparative fit index = 0.968; root mean square error of approximation = 0.08). Concurrent validity met prespecified hypotheses, indicating similarity of concepts with the PSQI (correlation [ r ] = 0.627) and N‐QOL ( r  = −0.784) total scores. The INTU differentiated among patients with different nocturic episode frequencies ( P  < 0.05 for all three summary scores). Statistically significant decreases were observed in mean Overall and Nighttime Impact Scores at week 2 versus week 1 in responders, indicating that the instrument can detect changes in response to symptom improvements. Conclusions: The INTU questionnaire demonstrated robust measurement properties and is a suitable tool for assessing the patient‐reported impact of nocturia on health and functioning.